2021
DOI: 10.3390/ijerph18094968
|View full text |Cite
|
Sign up to set email alerts
|

Seaweeds as Valuable Sources of Essential Fatty Acids for Human Nutrition

Abstract: The overexploitation of terrestrial habitats, combined with the ever-growing demand for food, has led to the search for alternative food sources. The importance of seaweeds as food sources has been growing, and their potential as sources of fatty acids (FA) make seaweeds an interesting feedstock for the food and nutraceutical industries. The aim of this study is to assess the potential of five red seaweeds (Asparagospis armata, Calliblepharis jubata, Chondracanthus teedei var. lusitanicus, Gracilaria gracilis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 92 publications
2
22
0
1
Order By: Relevance
“…The total fat content in the dried samples of both species was low (0.55–0.82 g/100 g DW). However, despite the low total lipid concentration, they contain significant amounts of essential mono- and poly-unsaturated fatty acids and offer many beneficial effects on human health [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The total fat content in the dried samples of both species was low (0.55–0.82 g/100 g DW). However, despite the low total lipid concentration, they contain significant amounts of essential mono- and poly-unsaturated fatty acids and offer many beneficial effects on human health [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…These extracts need to be further tested for the development of novel active products for skin care and treatment. Additional studies should also be oriented to the evaluation of a similar processing scheme for seaweeds with a higher content of ω-3 PUFAs [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the seaweed U. pinnatifida harvested in central Portugal (Figueira da Foz, Buarcos bay) in January 2020 unveiled a different fatty acid profile, presenting the SFA C18:0, the MUFA C15:1, and the PUFA C20:4 [95], while S. latissima harvested in March of 2017 in Norway revealed a varied outline of fatty acids, presenting the SFA C17:0 and C18:0, as well as PUFA, such as C18:2 ω-6, C20:4 ω-6, and C18:4 ω-3 [96]. Other teams of researchers found that Saccharina latissima (July-summer), Saccorhiza polyschides (January-winter) and Laminaria ochroleuca (September-summer) collected in the north of Portugal (Viana do Castelo) presented a different fatty acid profile depending on the harvesting season [97].…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids are essential components of cell membranes that play crucial roles as energy sources in body growth and development [95,98,99]. Polyunsaturated fatty acids (PUFAs) ω-3 and ω-6 make up a significant amount of seaweed lipids, despite their modest crude lipid content.…”
Section: Discussionmentioning
confidence: 99%